The Association Between Happiness and Self-Rated Physical Health of African American Men: A Population-Based Cross-Sectional Study - George Mwinnyaa BA; Tichelle Porch MHS; Janice Bowie PhD; Roland J. Thorpe PhD (American Journal of Men's Health, 2018)
Happiness and self-rated physical health are included in national surveys to assess health perceptions and subjective well-being among individuals. Studies have reported that happiness impacts physical health; however, little is known about the association between happiness and self-rated physical health among African American men (AAM). The objective of this study is to examine this relationship. Participants were 1,263 AAM aged 18+ years from the National Survey of American Life who rated their happiness and physical health. Interviews were conducted between 2001 and 2003. Self-rated physical health was defined as how individuals rated their own physical health and happiness as how individuals perceived their subjective well-being. Three multivariate logistic regression models were used to examine the relationships between happiness and self-rated physical health. It was observed that AAM who were happy were more likely to be married, to be employed, and earn more than $30,000 annually compared to AAM who were not happy. AAM who were happy were less likely to rate their physical health as fair/poor relative to AAM who were not happy. When controlling for demographic and socioeconomic factors, AAM who reported being happy had lower odds of rating their physical health as fair/poor compared to AAM who reported not being happy. Findings suggest that AAM who are happy report better physical health than those who report not being happy. Public health promotion strategies focusing on AAM should consider happiness as a promising influence that may positively impact physical health.